Implementation of Online Learning for Children with Language Disorder During the COVID-19 Pandemic: A Case Study in Inclusive Primary Schools - Uswatun - Hasanah; Asep - Supena (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2021)
Children with language disorder must receive special attention during online learning during a pandemic. This study aims to explore the perceptions of inclusive elementary school teachers on the implementation of online learning for children with language disorders during the COVID-19 pandemic. Data collection was carried out through surveys and semi-structured interviews with 38 inclusive primary school teachers spread across the South Jakarta area. Data analysis using thematic analysis of qualitative data. The results of the analysis found three main themes, namely, the selection of teaching media, learning methods, and learning assessments. The results of this study indicate that the success of online learning for children with language disorders depends on the involvement of teachers and parents in guiding students. Parents must be actively involved in supporting and guiding children during the learning process at home, while teachers must be creative and innovative in creating fun learning for children, especially children with language disorders. This research can also be a reference for future researchers to develop a learning model that is appropriate for implementation during the pandemic period.Keywords: language disorder, online learning, COVID-19